2019
DOI: 10.1002/jcc.25867
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of anticancer drug delivery from carbon nanotube using metal nanowires

Abstract: In this study, we have investigated delivery of cisplatin as the anticancer drug molecules in different carbon nanotubes (CNTs) in the gas phase using molecular dynamics simulation. We examined the shape and composition of the releasing agent by using the different nanowires and nanoclusters. We also investigated the doping effect on the drug delivery process using N-, Si, B-, and Fe-doped CNTs. Different thermodynamics, structural, and dynamical properties have been studied by using the pure and different dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As this figure shows, the low (3%) doped systems are not more stable than the pure CNT system whereas the high (20%) doped systems have higher absolute total energies (and are more stable) then the pure system. The more instability of the low doped CNT systems can be due to the nonuniformity of the bond distributions in the doped CNTs than the pure nanotubes. , The more stability of high doped CNTs can be due to the stronger interactions between the doped atoms and the confined water molecules than the carbon–water interactions in the pure system. It is also shown in Figure that the high N-doped CNT is the most stable system than the other CNT systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As this figure shows, the low (3%) doped systems are not more stable than the pure CNT system whereas the high (20%) doped systems have higher absolute total energies (and are more stable) then the pure system. The more instability of the low doped CNT systems can be due to the nonuniformity of the bond distributions in the doped CNTs than the pure nanotubes. , The more stability of high doped CNTs can be due to the stronger interactions between the doped atoms and the confined water molecules than the carbon–water interactions in the pure system. It is also shown in Figure that the high N-doped CNT is the most stable system than the other CNT systems.…”
Section: Resultsmentioning
confidence: 99%
“…The more instability of the low doped CNT systems can be due to the nonuniformity of the bond distributions in the doped CNTs than the pure nanotubes. 67,68 The more stability of high doped CNTs can be due to the stronger interactions between the doped atoms and the confined water molecules than the carbon−water interactions in the pure system. It is also shown in Figure 7 that the high N-doped CNT is the most stable system than the other CNT systems.…”
Section: Phase Change Of Confined Water Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that the metal doping of CNTs can affect the different properties of the confined molecules. 48 …”
Section: Simulation Detailsmentioning
confidence: 99%
“…Chemotherapy is a type of cancer therapy that uses one or more anticancer drugs to destroy or control tumors. Although the numerous number of anticancer drugs have been used extensively in clinical trials, the single‐agent chemotherapy commonly suffers from low in vivo potency due to the physiological complexity of various cancer cells .…”
Section: Introductionmentioning
confidence: 99%